Does Free Secondary Education Mitigate The Impact Of Teen Births On Educational Outcomes? Evidence From Ghana. - Tabiri, K.G.; Tahiru, M.; Atakorah, Y.B.; Novignon, J. (Social Sciences & Humanities Open, 2025)
Teenage pregnancy and early childbirth have potential implications for human capital development that can transcend the teen mothers to their children. Using data from the latest demographic and health survey data from Ghana, this study set out to understand how teen births affect the educational attainment of the mother, and how a policy that reduces the financial cost of senior high school education could moderate this effect. We used instrumental variables to account for endogeneity of teen births. Our results show that teen birth has a negative impact on the educational attainment of the mother. Furthermore, a program that reduced the financial cost of senior secondary education helped attenuate this negative impact for girls in urban areas but had no such effect for girls in rural areas. Our findings emphasize the need to intensify efforts to provide support systems for teen mothers that will enable their reintegration into school after childbirth. They also point out the importance of targeting such interventions to ensure that they address groups of people with peculiar challenges including relatively poor infrastructure, economic conditions and cultural practices/beliefs that facilitate risky sexual behavior.
Research Article
Keywords: Teen Childbirth; Educational Attainment; Instrumental Variable; Ghana; Free Secondary Education; Sub-Saharan Africa